Media use in digital everyday life - Ytre-Arne, Brita (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. As digital technologies have become ever more ingrained in society, Media Use in Digital Everyday Life asks how our relationship with media has changed. After the proliferation of smartphones, social media and ubiquitous connectivity, what has happened to the ways we navigate across social domains and structure our daily routines? Filling a gap between classic discussions on everyday media use and recent studies of emergent technologies, this book untangles how media become meaningful to us in the everyday, connecting us to communities and publics. With analyses of media use in an ordinary day, as part of life transitions and in times of disruption, Ytre-Arne provides a comprehensive framework for studies of everyday media use, considering dilemmas of technological transformations and recent crises such as the COVID-19 pandemic. Media Use in Digital Everyday Life offers empirical, methodological and theoretical insight, building on extensive qualitative research and taking a cross-media perspective. Through the conceptual approaches of media repertoires and public connection, the book situates communication and changing media use in everyday contexts, showing how our more digital everyday lives intensify communicative dilemmas. Written in an accessible tone, Media Use in Digital Everyday Life will appeal to readers interested in digital media, and to students and scholars of audiences, datafication, journalism and digital platforms.
Keywords: Digital media -- Social aspects.; Information technology -- Social aspects.; Social Science -- Media Studies.; Media studies.; elektronické knihy; electronic books